Mobocertinib in patients with EGFR Exon 20 insertion-positive non-small cell lung cancer (MOON): an international real-world safety and efficacy analysis - Illini, Oliver; Saalfeld, Felix; Christopoulos, Petros; Duruisseaux, Michaël; Vikström, Anders; Peled, Nir; Demedts, Ingel; Dudnik, Elizabeth; Eisert, Anna; Hashemi, Sayed M. S.; Janzic, Urska; Kian, Waleed; et al. (International journal of molecular sciences, 2024)
EGFR exon 20 (EGFR Ex20) insertion mutations in non-small cell lung cancer (NSCLC) are insensitive to traditional EGFR tyrosine kinase inhibitors (TKIs). Mobocertinib is the only approved TKI specifically designed to target EGFR Ex20. We performed an international, real-world safety and efficacy analysis on patients with EGFR Ex20-positive NSCLC enrolled in a mobocertinib early access program. We explored the mechanisms of resistance by analyzing postprogression biopsies, as well as cross-resistance to amivantamab. Data from 86 patients with a median age of 67 years and a median of two prior lines of treatment were analyzed. Treatment-related adverse events (TRAEs) occurred in 95% of patients. Grade ≥3 TRAEs were reported in 38% of patients and included diarrhea (22%) and rash (8%). In 17% of patients, therapy was permanently discontinued, and two patients died due to TRAEs. Women were seven times more likely to discontinue treatment than men. In the overall cohort, the objective response rate to mobocertinib was 34% (95% CI, 24-45). The response rate in treatment-naïve patients was 27% (95% CI, 8-58). The median progression-free and overall survival was 5 months (95% CI, 3.5-6.5) and 12 months (95% CI, 6.8-17.2), respectively. The intracranial response rate was limited (13%), and one-third of disease progression cases involved the brain. Mobocertinib also showed antitumor activity following EGFR Ex20-specific therapy and vice versa. Potential mechanisms of resistance to mobocertinib included amplifications in MET, PIK3CA, and NRAS. Mobocertinib demonstrated meaningful efficacy in a real-world setting but was associated with considerable gastrointestinal and cutaneous toxicity.